The Privacy of Summary Proceeding (The International Journal for Scientific Research, 2024)
The research focuses on the privacy of summary proceeding, where the research is divided into three sections. The first section discusses the deadlines for summary proceeding, highlighting the dates for considering summary petition claims and its termination dates for issuing judgments in summary cases, also revealing objection deadlines by relying on both civil procedure and commercial courts of law in summary petition. Moreover, the research has examined cases of lapse of summary judgments, mentioning the reasons for the invalidation of the summary request, such as delay in submitting the original request, abandonment of the claim, and considering the judgment as if it did not exist.The researchers also discuss the reasons that entitle the interested party to request the cancellation of the summary judgment, which are determined through various cases, including the dismissal of the claim, the cessation of the urgent situation, and the suspension of the case’s proceedings. Ultimately, the research highlights a judicial ruling stating that if the plaintiff is absent from the court session, the fate of the judgment issued by the judge is the rejection of the claim. Therefore, the plaintiff must attend the trial sessions in order to obtain a judgment that protects their rights expeditiously until the matter is considered by the regular judiciary.
Keywords: the Privacy of Summary Proceeding; the Deadlines for Summary Proceeding; Cases of Summary Proceeding